Hypertension in women: the role of progesterone and aldosterone - Boschitsch, E.; Mayerhofer, S.; Magometschnigg, D. (Climacteric : the journal of the International Menopause Society, 2010)
The age-related course of blood pressure and its gender-related difference, as well as the incidence of hypertension, have been the subject of multiple experimental, clinical and epidemiological studies over the past decades. The role of the sex hormones estradiol and testosterone within this gender dimorphism has been investigated without conclusive results. In this review, we provide background information on the gender difference in blood pressure, describe the impact of progesterone and aldosterone, and discuss the pathophysiology of aldosteronism as well as the potential role of drospirenone as a gender-specific agent for the prevention and treatment of hypertension and for cardiovascular protection.